Effects of blue light emitting diode (led) and doxycycline to sebaceous gland in acne vulgaris - Listiawan, M Yulianto; Prakoeswa, Cita Rosita Sigit; Handamari, Dhyah Aksarani; Indira, Regitta (Folia Medica Indonesiana, 2017)
Acne vulgaris (AV) is an inflammation of pilosebaceous unit especially in young adult. The pathophysiology is the elevation of sebum production, keratinization of abnormal pilocebaseous follicles, and inflammation caused by immune response to Propionibacterium acnes. Therapy combination of oral antibiotics (doxycycline) and physical therapy (blue light) in moderate-severe acne is one option to reduce antibiotic resistance. Doxycycline is a commonly antibiotic used. The effects of photosensitive can increase the penetration of blue light by sebaceous glands. There was a total decrease in sebum and clinical improvement of combination therapy of blue light and doxycycline in seven patients. The combination therapy has been shown to improve its therapeutic effect, but more clinical trials are needed to prove the effectiveness of blue light with doxycycline than without blue light.